Slow deep breathing and acupressure massage on fatigue and oxygen saturation in patients with chronic renal failure undergoing hemodialysis - Sudrajat, Sudrajat; Umeda, Miciko; Sulaeman, Suhendar (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Breathing exercise can provide a positive effect for patients with chronic renal failure (CRF), because it can increase development of lung and will increase the consentration of oxygen in the blood so that oxygen need it. Accupresure will stimulate and rebuild the cells in the body are weakened and imporve blood circulation in the body, as to reduce tension and fatigue.Purpose: To determine the effect of breathing exercises and acupressure on the level of fatigue and oxygen saturation of CRF patients.Method: Quasy experiment with 20 participants, instrument is used to fatigue assesment scale (FAS), fatigue and saturation oxygen obsevation sheet. This research is implementated in hemodialysis room at Serang Hospital.Results: There was a significant different of level fatigue before and after breathing exercise (p=0.005), significant different of level fatigue before and after breathing exercise and acupresure (p=0.014), and there significant different of oxygen saturation before and after breathing exercise and before and after breathing exercise and acupresure (p=0.108).Conclusion: Exercise breathing in people with chronic renal failure can alter how tired they feel, and as a result, there is a big difference in how tired they feel before and after exercising while taking deep breaths.